Simple floating inductance simulators using OTAs - Petchmaneelumka, Wandee (My University, 2009)
This paper presents a simple technique to realize floating inductance simulators using commercial and low-cost devices. Both negative and positive floating inductances can be obtained in the same scheme without stability problem. The realization method based on the use of operational transconductance amplifiers (OTAs) and one grounded capacitor provides the advantage of an electronic tuning capability. The resulting inductance can be electronically adjusted by changing external bias currents of OTAs. Experimental results demonstrating the circuit performances based on the use of commercially available OTAs are included. © 2009 IEEE.
Keywords: Floating inductance simulator; Negative inductance; OTA